Increased urinary exosomal SYT17 levels in chronic active antibody-mediated rejection after kidney transplantation via the IL-6 amplifier. (5th May 2020) - Takada, Yusuke; Kamimura, Daisuke; Jiang, Jing-Jing; Higuchi, Haruka; Iwami, Daiki; Hotta, Kiyohiko; Tanaka, Yuki; Ota, Mitsutoshi; Higuchi, Madoka; Nishio, Saori; Atsumi, Tatsuya; Shinohara, Nobuo; et al.
Abstract: Chronic active antibody-mediated rejection (CAAMR) is a particular problem in kidney transplantation (KTx), and ~25% of grafts are lost by CAAMR. Further, the pathogenesis remains unclear, and there is no effective cure or marker. We previously found that a hyper NFκB-activating mechanism in non-immune cells, called the IL-6 amplifier, is induced by the co-activation of NFκB and STAT3, and that this activation can develop various chronic inflammatory diseases. Here, we show that synaptotagmin-17 (SYT17) is increased in an exosomal fraction of the urine from CAAMR patients, and that this increase is associated with activation of the IL-6 amplifier. Immunohistochemistry showed that SYT17 protein expression was increased in renal tubule cells of the CAAMR group. While SYT17 protein was not detectable in whole-urine samples by western blotting, urinary exosomal SYT17 levels were significantly elevated in the CAAMR group compared to three other histology groups (normal, interstitial fibrosis and tubular atrophy, and calcineurin inhibitors toxicity) after KTx. On the other hand, current clinical laboratory data could not differentiate the CAAMR group from these groups. These data suggest that urinary exosomal SYT17 is a potential diagnostic marker for CAAMR. Abstract : Urinary exosomal SYT17 as a biomarker for kidney rejection